Myths and facts in the chronicles of the conquest of Ancient Peru - Portugal, Ana Raquel [UNESP] (Univ do Vale do Rio Dos Sinos, 2010)
The chronicles of historical sources are difficult because they are a mix of myths and facts experienced by their authors. Starting from this premise, this study analyzes some of the Spanish and indigenous sources on the conquest of the Inca people and the description of this world and people who were so different. Among the chroniclers chosen, the article highlights the reports by Jose de Acosta on the Mundus Novus and by Cieza de Leon and Garcilaso de la Vega on the myths of the first Inca chief; finally, Francisco de Xerez, Juan de Betanzos, among others, on the event of the imprisonment and murder of Atahualpa, which resulted in the conquest of the "Tahuantinsuyu" by the Spanish.
Keywords: myths; facts; chronicles